2008
DOI: 10.2353/ajpath.2008.070416
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-C, a Potential Paracrine Regulator of Glomerular Permeability, Increases Glomerular Endothelial Cell Monolayer Integrity and Intracellular Calcium

Abstract: We have previously reported expression of vascular endothelial growth factor (VEGF)-A and -C in glomerular podocytes and actions of VEGF-A on glomerular endothelial cells (GEnC) that express VEGF receptor-2 (VEGFR-2). Here we define VEGFR-3 expression in GEnC and investigate the effects of the ligand VEGF-C. Renal cortex and cultured GEnC were examined by microscopy, and both cell and glomerular lysates were assessed by Western blotting. VEGF-C effects on trans-endothelial electrical resistance and albumin flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Schumacher et al[ 13] describe the downregulation of VEGF 165 b mRNA expression in laser-microdissected glomeruli from patients with Denys-Drash disease, whilst high levels of conventional VEGF 165 remain and, as a result, the glomeruli are not capable of developing passed the s-shaped body stage. Another potential player in glomerular disease from the VEGF family of proteins is VEGF-C. We have demonstrated the expression of VEGF-C by podocytes, which has functional effects on both cultured GEnC and podocytes [14, 15]. Interestingly, VEGF-C activates VEGFR2 not VEGFR3 in cultured GEnC resulting in a reduction in macromolecular passage, which is in sharp contrast to the increased macromolecular passage by VEGF-A [14].…”
Section: Vegf Within the Glomerulusmentioning
confidence: 91%
See 1 more Smart Citation
“…Schumacher et al[ 13] describe the downregulation of VEGF 165 b mRNA expression in laser-microdissected glomeruli from patients with Denys-Drash disease, whilst high levels of conventional VEGF 165 remain and, as a result, the glomeruli are not capable of developing passed the s-shaped body stage. Another potential player in glomerular disease from the VEGF family of proteins is VEGF-C. We have demonstrated the expression of VEGF-C by podocytes, which has functional effects on both cultured GEnC and podocytes [14, 15]. Interestingly, VEGF-C activates VEGFR2 not VEGFR3 in cultured GEnC resulting in a reduction in macromolecular passage, which is in sharp contrast to the increased macromolecular passage by VEGF-A [14].…”
Section: Vegf Within the Glomerulusmentioning
confidence: 91%
“…Another potential player in glomerular disease from the VEGF family of proteins is VEGF-C. We have demonstrated the expression of VEGF-C by podocytes, which has functional effects on both cultured GEnC and podocytes [14, 15]. Interestingly, VEGF-C activates VEGFR2 not VEGFR3 in cultured GEnC resulting in a reduction in macromolecular passage, which is in sharp contrast to the increased macromolecular passage by VEGF-A [14]. Therefore, VEGF-C has the potential to affect the local dosage of glomerular VEGF-A by competing with signalling effects through the same receptor.…”
Section: Vegf Within the Glomerulusmentioning
confidence: 99%
“…Podocytes are the main source of VEGF in glomeruli [14]. Glomerular endothelial cells express VEGF receptors (VEGFR) 2 and VEGFR3 [12,15]. Reduced endothelial fenestration is a known finding in conditions with severe endothelial injury, such as preeclampsia and hemolytic uremic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested there was another receptor binding VEGF-C in podocytes. The same scientific team, but in a different publication, proved VEGF-C to increase glomerular cell monolayer integrity via VEGFR-2, and observed glomerular ECs to express VEGFR-3 in tissue sections and culture [16].…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%